The intellectual origins of the European Reformation - McGrath, Alister Edgar, 1953- (Malden, MA Blackwell, 2004)
Includes bibliographical references and index.
Keywords: Reformation; Theology, doctrinal -- history -- Middle Ages, 600-1500.; Europe -- intellectual life -- history -- Middle Ages, 600-1500.